Corpo e responsividade: implicações éticas da fenomenologia da percepção - Carboni, Paulo Henrique (2021)
Our object of investigation is the possible description of the ethical sense in Merleau-Ponty's Phenomenology of Perception. With Husserl, the philosopher approaches perception from a phenomenological point of view and criticizes a rationality that is separate from the world. This split emerges from empiricist and intellectual understandings of reality. The philosopher offers his criticism by describing perception as our access to the world. This implies that perception has its own cogito, prior to that of objective reflexivity. The result of Merleau-Ponty's investigation is the evidence of the body, described as one’s own body, and the relationship of this body schema to the environment. From here, the philosopher reflects from the standpoint of an incarnate thought, which means a certain review of elements that have been constituted throughout the history of philosophy. Understanding, Philosophy and life are then taken up from the perspective of a reflection on the perceptual cogito. In this debate, it seemed to us that Bernhard Waldenfels' writings converged with Merleau-Ponty's thinking. Waldenfels described a responsive phenomenology proper to the hyperphenomenon of the stranger (Fremd). From this responsive phenomenology, the ethical character of the response to an appeal is evident. We describe, then, the implication of a phenomenology of responsiveness in the Phenomenology of Perception in order to highlight the ethical sense that is established with this strange otherness that is the world that surrounds us.